Management and Outcomes in Children with Third-Generation Cephalosporin-Resistant Urinary Tract Infections. (17th February 2021) - Wang, Marie E; Greenhow, Tara L; Lee, Vivian; Beck, Jimmy; Bendel-Stenzel, Michael; Hames, Nicole; McDaniel, Corrie E; King, Erin E; Sherry, Whitney; Parmar, Deepika; Patrizi, Sara T; Srinivas, Nivedita; et al.
Abstract: Background: Third-generation cephalosporin-resistant urinary tract infections (UTIs) often have limited oral antibiotic options with some children receiving prolonged parenteral courses. Our objectives were to determine predictors of long parenteral therapy and the association between parenteral therapy duration and UTI relapse in children with third-generation cephalosporin-resistant UTIs. Methods: We conducted a multisite retrospective cohort study of children <18 years presenting to acute care at 5 children's hospitals and a large managed care organization from 2012 to 2017 with a third-generation cephalosporin-resistant UTI from Escherichia coli or Klebsiella spp. Long parenteral therapy was ≥3 days and short/no parenteral therapy was 0–2 days of concordant parenteral antibiotics. Discordant therapy was antibiotics to which the pathogen was non-susceptible. Relapse was a UTI from the same organism within 30 days. Results: Of the 482 children included, 81% were female and the median age was 3.3 years (interquartile range: 0.8-8). Fifty-four children (11.2%) received long parenteral therapy (median duration: 7 days). Predictors of long parenteral therapy included age <2 months (adjusted odds ratio [aOR] 67.3; 95% confidence interval [CI]: 16.4-275.7), limited oral antibiotic options (aOR 5.9; 95% CI: 2.8-12.3), and genitourinary abnormalities (aOR 5.4; 95% CI: 1.8-15.9). UTI relapse occurred in 1 of the 54 (1.9%) children treated with long parenteral therapy and in 6 of the 428 (1.5%) children treated with short/no parenteral therapy ( P  = .57). Of the 105 children treated exclusively with discordant antibiotics, 3 (2.9%, 95% CI: 0.6%-8.1%) experienced UTI relapse. Conclusions: Long parenteral therapy was associated with age <2 months, limited oral antibiotic options, and genitourinary abnormalities. UTI relapse was rare and not associated with duration of parenteral therapy. For UTIs with limited oral options, further research is needed on the effectiveness of continued discordant therapy. Abstract : Among 482 children with urinary tract infections (UTIs) resistant to third-generation cephalosporins, parenteral therapy courses ≥3 days were common in infants <2 months of age but uncommon (8%) in older children. UTI relapse was rare and not associated with duration of parenteral therapy.